Participativni pristop pri pripravi upravljavskih načrtov na primeru izbranih gozdnih habitatnih tipov in živalskih vrst ob Muri - Andreja Ferreira (Slovenian Forestry Institute, 2021)
For Natura 2000 areas, the European Commission proposes the drafting of management plans that include site-specific objectives and conservation measures based thereon. In order to avoid potential subsequent conflicts, the process needs to involve all stakeholders early on and in a sensible manner. In the framework of the project GoForMura, management plans for the Natura 2000 forest sites in the study areas of Gornja Bistrica and Murska Šuma in the Prekmurje region were drafted as model plans. The participation of stakeholders, in particular forest owners and managers, was given special attention in the drafting of what were the first such documents.